A case–control study assessing bone mineral density in severe haemophilia A in the UK. (7th November 2014) - Wells, A. J.; McLaughlin, P.; Simmonds, J.V.; Prouse, P. J.; Prelevic, G.; Gill, S.; Chowdary, P.
Summary It has been shown that bone mineral density (BMD) may be lower in patients with haemophilia (PWH). A comparison to control subjects is required to thoroughly assess current BMD in PWH in the UK. The objective of this study was to test the hypothesis that BMD is lower in PWH than in controls, and in patients with more severely affected joints or lower activity levels. In this case–control study, 37 patients with severe haemophilia A were recruited from two haemophilia centres in the UK. A group of 37 age, gender and ethnicity‐matched control participants were recruited. All participants had a bone density scan, a musculoskeletal assessment, a blood test for vitamin D and completed a functional activity questionnaire. Of the case group, 5% had osteoporosis and 24% had BMD lower than expected for age. No control participants had osteoporosis, 3% had osteopenia and 14% had BMD lower than expected for age. Ninety one per cent of case participants and 92% of control participants had reduced 25(OH)D levels. Case participants had significantly lower BMD than control participants, and case participants with more severely affected joints, lower activity levels, HIV, history of hepatitis C or lower BMI had significantly lower BMD. Patients with severe haemophilia have a higher risk of low BMD than men without haemophilia. Patients with more severely affected joints and lower activity levels have lower BMD. It remains unclear whether patients with low BMD reached adequate peak bone mass. Low vitamin D may be present in the majority of PWH.